-36=3(w-6)-5w

Simple and best practice solution for -36=3(w-6)-5w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -36=3(w-6)-5w equation:



-36=3(w-6)-5w
We move all terms to the left:
-36-(3(w-6)-5w)=0
We calculate terms in parentheses: -(3(w-6)-5w), so:
3(w-6)-5w
We add all the numbers together, and all the variables
-5w+3(w-6)
We multiply parentheses
-5w+3w-18
We add all the numbers together, and all the variables
-2w-18
Back to the equation:
-(-2w-18)
We get rid of parentheses
2w+18-36=0
We add all the numbers together, and all the variables
2w-18=0
We move all terms containing w to the left, all other terms to the right
2w=18
w=18/2
w=9

See similar equations:

| -5x-3=-9 | | −17c=21 | | 8(y+4)-2(y-1)=10-3(y-20) | | –6(2r+8)+7r+1=–10(r–3)–3(8–r) | | 7=−3x−2−6x | | 3(x-2)-5(2x+)=3 | | 3(2x−5)−4x+8=−2x+13(2x−5)−4x+8=−2x+13(2x−5)−4x+8=−2x+13(2x−5)−4x+8=−2x+13(2x−5)−4x+8=−2x+13(2x−5)−4x+8=−2x+13(2x−5)−4x+8=−2x+1 | | 3x-4-3=11 | | 18-b=-5b+7b | | 3(2x−5)−4x+8=−2x+1 | | 3(v+5)+3v=-3 | | 10+2x=2-12(x+1) | | 16.6=16.6=  x+15.8x+15.8 | | 2x-20-5x=x+5+x | | 2(6x-4)=3(6x+2 | | 7a+7a+(a+15)=180 | | -3(x+4)=6x+6(1-x) | | -3(2n+4n)=-102 | | –2y+6=4 | | -4(4x+3)=20 | | -5+25x+-40x-10=-7x-2x-7x | | 7r-6=3-r+7 | | 3.5s=6 | | (3m–10)–(6m+2)=-3m-12 | | 6y+6=90 | | v-4.6=9.8 | | 3y-1=-5(-3+y) | | 6-3d=-3(d-2) | | 0.4x+1.6=0.8x-0.4 | | -3x=8x+434 | | 5x+4(x+1)=x | | 1+7n=9+5n |

Equations solver categories